P529 Evolution of COVID19 serology in a real-life population of IMID patients. Results of the BELCOMID study: BELgian Cohort study of COVID-19 in Immune Mediated Inflammatory Diseases (IMID). (21st January 2022) - Geldof, J; Sabino, J; Ferrante, M; Lambert, J; Lapeere, H; Hillary, T; Van Laethem, A; De Vlam, K; Verschueren, P; Lobaton, T; Vermeire, S
Abstract: Background: Immunomodulators (IMM) and Targeted Immune-Modulating Therapies (TIMT) such as anti-TNF, anti-interleukins and Janus Kinase inhibitors, for treatment of Immune Mediated Inflammatory diseases (IMID) could theoretically interfere with the cytokine storm and humoral immune response against COVID19 infection and vaccination. We investigate seroprevalence and evolution of SARS-CoV2 antibodies in relation to previous vaccination and/or exposure to COVID19 and ongoing IMID-treatment in a Belgian, real-life population of IMID patients. Methods: A cross-disciplinary, prospective, observational cohort study was set up at two university hospitals. All patients with IMIDs of the gut (Crohn's disease, ulcerative colitis), joints (rheumatoid, psoriatic or spondyloarthritis) and skin (psoriasis, hidradenitis suppurativa, atopic dermatitis) visiting the respective clinics were asked to participate. Patients had to fill out an electronic survey (REDCap®, based on WHO-ISARIC) and blood samples were drawn for serology testing (anti-Spike(S) and anti-viral Nucleocapsid(N) protein antibody IgG, Abbott). Results at baseline, prior to the national vaccination program and at 6 months follow-up are presented. R version 4.0.2 was used for statistical analyses. Results: At baseline 2165 IMID patients consented to take part. In 3.2% SARS-CoV2 anti-N seroconversion was confirmed. Of the anti-N seroconverted patients 72.9% reported a positive PCR test prior to inclusion. At 6-months follow-up, data of 1853 IMID patients was collected. Of these, 81.7% were fully and 14.4% partially vaccinated. Seroconversion for anti-N antibodies was confirmed in 2.5% of all participants and seroconversion for anti-S antibodies in 90.8%. In 5.1% (61/1483) of fully vaccinated IMID patients no seroconversion in anti-N nor anti-S antibodies was found. Chi Square analyses show, at 6-months follow-up, no significant association between anti-S seroconversion rate and treatment with systemic steroids (RiskRatio 1.22, 95%CI 0.38–3.9, P=0.99), TIMT (RiskRatio 0.57, 95% CI 0.3–1.1, P=0.12), IMM (RiskRatio 1.65, 95% CI 0.85–3.19, P=0.19) or combination treatment IMM/TIMT (RiskRatio 1.60, 95% CI 0.75–3.4, P=0.32). Appearance of COVID19 symptoms followed the epidemiological curve in Belgium (Fig1). Conclusion: In this real-life IMID cohort, the number of COVID19 cases confirmed by PCR prior to vaccination was low. Seroconversion rate for anti-N antibodies was lower at 6-months follow-up, suggesting decrease in antibody titre over time. Full COVID19 vaccination led to a high anti-S antibody seroconversion rate. Nonetheless, 5.1% of fully vaccinated patients showed no antibody seroconversion. So far, no significant association between anti-S antibody seroconversion and IMID treatment was noted.